2013
DOI: 10.1111/jam.12154
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of internalized Salmonella Typhimurium in lettuce and green onion using ultraviolet C irradiation and chemical sanitizers

Abstract: Aims: The internalized human pathogens in fresh produce are not effectively removed during conventional washing, and therefore, it may cause foodborne illness when the produce is consumed raw. Thus, effective nonthermal processes are needed to prevent this risk. Methods and Results: Green fluorescence protein-tagged Salmonella Typhimurium was either sprayed on the surface of iceberg lettuce or injected into the bottom part (bulb) of green onions to induce bacterial internalization. The contaminated vegetables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…For example using ultraviolet C irradiation and chemical sanitizers were very efficient to disinfected lettuce and fresh vegetable. Recent studies showed that ionizing radiation, such as gamma ray and electric beam, has been frequently examined for its potential of inactivating the internalized pathogens in fresh produce (Chimbombi et al 2011;Ge et al, 2013) and it was shown as an effective physical disinfectant to inactivate the human pathogens with low fluency in food without generating toxic hazards or making food radioactive, which has been confirmed by World Health Organization. Compared with the ionizing radiation methods, the application of ultraviolet light has grown steadily in various fields such as water, wastewater, aerosol, surface and food as its germicidal effect was firstly described by Ge et al (2013).…”
Section: Iiiprevention : 1 Foods and Watermentioning
confidence: 96%
See 1 more Smart Citation
“…For example using ultraviolet C irradiation and chemical sanitizers were very efficient to disinfected lettuce and fresh vegetable. Recent studies showed that ionizing radiation, such as gamma ray and electric beam, has been frequently examined for its potential of inactivating the internalized pathogens in fresh produce (Chimbombi et al 2011;Ge et al, 2013) and it was shown as an effective physical disinfectant to inactivate the human pathogens with low fluency in food without generating toxic hazards or making food radioactive, which has been confirmed by World Health Organization. Compared with the ionizing radiation methods, the application of ultraviolet light has grown steadily in various fields such as water, wastewater, aerosol, surface and food as its germicidal effect was firstly described by Ge et al (2013).…”
Section: Iiiprevention : 1 Foods and Watermentioning
confidence: 96%
“…Foods susceptible to transport Salmonella include vegetable products such as lettuce. The fresh produce consumption is encouraged because of its health benefits; however, fresh produce can be contaminated with human pathogens in any stage of the food supply chain, which increases the risk of foodborne outbreaks (Lynch et al, 2009;Ge et al, 2013). Hygienic conditions are needed for these fresh produce for consumption to avoid contamination.…”
Section: Mode Of Transmissionmentioning
confidence: 99%
“…Internalized bacteria can evade disinfection, thus detailed study on the mechanism of internalization as well as on plant and environmental factors affecting internalization is needed to devise remediation methods ensuring safety of the fresh produces (Ge et al 2013). Mechanism of internalization of bacteria in the plant has not been elucidated clearly till now.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of using irradiation in foods include its ability to eliminate food-borne pathogens or bacteria internalized in produce relative to chemical washes such as chlorine dioxide, sodium hypochlorite or other nonoxidizing agents which do not readily affect internalized microbes (Ge, Bohrerova, & Lee, 2013;Gomes, Da Silva, Moreira, & CastellPerez, 2009;Niemira, 2007;Shim et al, 2012). Irradiation has also been reported to extend the shelf life of produce and reduce quality losses in food or produce especially during short or longdistance transport in addition to its role in food safety (Prakash, Inthajak, Hulbregtse, Caporaso, & Foley, 2000).…”
Section: Introductionmentioning
confidence: 97%